Ticības un prāta attiecības indiešu filosofa Svami Šivanandas darbos - Segleniece, Sanda (Latvijas Universitāte, 2007)
Bakalaura darbā atspoguļota indiešu Filosofa Šrī Svami Šivanandas Sarasvati izpratne par ticību un prātu, kā arī šo terminu vienojošie aspekti. Darbā iekļauti arī dažādi Dieva eksistences argumenti un to skaidrojumi Šivanandas darbos un dažādu Rietumu reliģijas filozofu uzskatos, kā arī kristietības pamatnostādnēs. Darbā dots skaidrojums kā prāta dažādie aspekti ietekmē cilvēka Dzīvi un kādas ir iespējas kontrolēt prātu. Cilvēka dievišķība Šivanandas darbos pretstatīta cilvēka grēcīgumam kristietībā. Lūgšanas – tiek uzskatītas par vienu no veidiem kā cilvēks var attīrīt prātu un sasniegt vienotību ar Dievu.

RELATION OF FAITH AND MIND IN THE BOOKS OF INDIAN PHILOSOPHER SRI SWAMI SIVANANDA. The comprehension of faith and mind as well as the uniting aspects of these terms are reflected in my Bachelor. The understanding of Different arguments of existence of God are also included and commented by different philosophers of religion comparing their attitude with the Christianity. Bachelor tries to give an explanation how the human life is affected by various aspects of mind. Sivananda and Christianity offer different concepts of God and man. Sivananda says that the only thing which keeps people away from God is ignorance, and the way out is the experience of unity with God. But Christianity explains that the main problem of people is sin, and this problem can be solved only by Help of Jesus Christ. Prayer is the easiest way to control mind and to reach the state of divinity
Relation of faith and mind in the books of Indian philosopher Sri Swami Sivananda
Keywords: Teoloģija un reliģiju zinātne